(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
The study was carried out to assess the genetic variation in indigenous turkey populations in South West Nigeria using seven protein markers: Hemoglobin (Hb), Albumin (Alb), Transferin (Tf), Esterase-1 (Es-1), Alkaline phosphatase (ALP), Carbonic anhydrase (CA), and Esterase-3 (Es-3).. A total of 97 turkey birds from Ibadan, Ijebu Ode and Akure were purposively sampled. Separation of plasma and red cell proteins were determined on cellulose acetate electrophoresis to estimate the genetic variability within and among the populations. The degree of heterozygosity, deviation from Hardy-Weinbergs Equilibrum (HWE), FIS, and FST values were estimated. From a total of 7 loci analyzed, six were found to be polymorphic in all the populations sampled while Es-1 was monomorphic. Two codominant alleles which controlled three different genotypes were observed at each polymorphic loci. Deviations from Hardy Weinberg equilibrium and a deficiency of heterozygotes were observed in all the populations. Average heterozygosities ranged between 0.13 and 0.20, heterozygote deficit FIT was estimated at 0.5784 while within breed deficit as evaluated by FIS ranged from 0.38 to 0.56. The fixation index FST revealed that genetic diversity within the studied population was moderately differentiated. Genetic distance among the populations quantified through calculation of Nei genetic distance ranged from 0.037 - 0.109. The result obtained may be used as an initial guide in defining objectives for future investigations of genetic integrity and developing conservation strategies for Nigeria indigenous turkeys.